1991
DOI: 10.1007/bf01708405
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine abnormalities in severe traumatic brain injury —a cue to prognosis in severe craniocerebral trauma?

Abstract: Patients with severe craniocerebral trauma (sCCT) display metabolic and endocrine changes. The question is raised whether hormonal patterns give cues to the prognosis of outcome or not. In 21 patients the function of the adrenocortical, gonadal, thyroid and human growth hormone (hGH)-insulin system was assessed. LH, FSH, TSH, prolactin and hGH were stimulated. 3 groups of patients were formed. Group I: patients in acute phase with a Glasgow Coma Score (GCS) more than 6 (group Ia) and less than 6 (group Ib). Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 23 publications
4
56
1
2
Order By: Relevance
“…In this regard, only a few authors have evaluated the relationship between outcome from TBI and the presence of pituitary dysfunction. As mentioned above, either positive or negative relationships between pituitary dysfunction and outcome from TBI have been observed in the early, acute phase post-TBI (41,46,47,61). We did not find any statistical correlation between outcome measures and presence of pituitary dysfunction, both in patients examined over a 5-year period after TBI (5) and in patients evaluated during the early rehabilitation period (48).…”
Section: Consequences and Treatment Of Pthpmentioning
confidence: 46%
See 2 more Smart Citations
“…In this regard, only a few authors have evaluated the relationship between outcome from TBI and the presence of pituitary dysfunction. As mentioned above, either positive or negative relationships between pituitary dysfunction and outcome from TBI have been observed in the early, acute phase post-TBI (41,46,47,61). We did not find any statistical correlation between outcome measures and presence of pituitary dysfunction, both in patients examined over a 5-year period after TBI (5) and in patients evaluated during the early rehabilitation period (48).…”
Section: Consequences and Treatment Of Pthpmentioning
confidence: 46%
“…A decrease in GH bursts frequency has been detected 24 -48 h after severe trauma, indicating a relative hyposomatotropinism (45). A blunted GH response to arginine (ARG) stimulation has been found in patients with severe TBI and very poor outcome (41). Gottardis et al (46) reported that a GH-releasing hormone (GHRH) test elicited a significant (43).…”
Section: Consequences Of Tbimentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, either positive or negative relationships between pituitary dysfunction and outcome from TBI have been observed in the early, acute phase post-TBI. (39,40,41,42) We did not find any statistical correlation between outcome measures and presence of pituitary dysfunction, both in patients examined over a 5-years period after TBI (5) and in patients evaluated during the early rehabilitation period. (43) Autopsy studies demonstrated a high incidence (14-74%) of anatomical lesions in the hypothalamic-pituitary region; this suggests, therefore, that hypopituitarism might contribute to the poor prognosis of the TBI patients.…”
Section: Consequencesmentioning
confidence: 62%
“…A number of studies have assessed the acute neuroendocrine changes following TBI, in order to investigate their correlation to trauma severity, metabolic derangement and variables that may predict outcome (Cernak et al, 1999;Cohan et al, 2005;Della et al, 1998;Feibel et al, 1983;Hackl et al, 1991). The clinical implications of these findings remain unclear.…”
Section: Prevalence Of Acute Hypopituitarism In Tbimentioning
confidence: 99%